2017
DOI: 10.1111/papr.12602
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Targeted Drug Delivery on‐Demand Bolus Option for Chronic Pain

Abstract: Utilizing an intrathecal bolus to treat incident pain was a safe way to manage unpredictable breakthrough pain and may represent a cost-saving opportunity by eliminating the need for oral analgesic medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The 2012 PACC recommendations suggested that patient‐controlled dosages be 5–20% of the total daily dosage. In a retrospective review from the Cleveland Clinic, up to 30% of the 24‐hour dose could be administered safely during each patient‐activated dose, up to four times daily . This represents a significantly larger incremental increase of the 24‐hour dose, suggesting that more prospective or retrospective data are required.…”
Section: Recommended Starting Dosagesmentioning
confidence: 99%
“…The 2012 PACC recommendations suggested that patient‐controlled dosages be 5–20% of the total daily dosage. In a retrospective review from the Cleveland Clinic, up to 30% of the 24‐hour dose could be administered safely during each patient‐activated dose, up to four times daily . This represents a significantly larger incremental increase of the 24‐hour dose, suggesting that more prospective or retrospective data are required.…”
Section: Recommended Starting Dosagesmentioning
confidence: 99%
“…For pain gene therapy, it is optimal to have the therapeutic analgesic molecule be delivered only to the pathological tissues and cells [72, 73] in order to reduce the side effects of treatment. DRG are a site in the peripheral somatosensory pathway that is critically involved in the development and maintenance of peripheral nerve injury-induced chronic pain [7476].…”
Section: Discussionmentioning
confidence: 99%
“…Although morphine or ziconotide monotherapy are the only medications approved by the Food and Drug Administration for use with this technology, there also is significant off-label use of other medications. Literature suggests that, by providing targeted drug delivery, intrathecal drug-delivery systems are more effective in controlling pain, with reduced side-effects, at a fraction of the dosing requirements of systemic opioids (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that an intrathecal drug-delivery system can eliminate or reduce the use of systemic opioids among patients with chronic noncancer pain (4)(5)(6)(7)(8)(9)(10)(11). Using commercial health insurance claims data from 2008 to 2011, we examined opioid discontinuation and all-cause healthcare utilization among patients newly implanted with an intrathecal drug-delivery system, finding that 51% of patients had eliminated use of systemic opioids at one year following intrathecal drug-delivery system implantation (9).…”
Section: Introductionmentioning
confidence: 99%